Analisis Dampak Pertambangan Terhadap Kehidupan Sosial Ekonomi Masyarakat Desa Ai Mual - Octaviani, Ismia; Supriadi, Supriadi (Lembaga Riset dan Publikasi, 2024)
This research is entitled. Analysis of the Impact of Mining on the Social and Economic Life of the Ai Mual Village Community in 2024. This research aims to understand more about the social and economic impact of the Ai Mual Village community after the mining. The method used in this research is a qualitative method with a descriptive approach, data collection techniques using observation, interviews and documentation. Before mining, Ai Mual Village was known for its traditional life which focused on agriculture, honey hunting and local community activities. The discovery of mining resources by local communities resulted in major shifts in the village's economic and social structure. Economic opportunities through opening up jobs and increasing income attract people to get involved in mining activities. The social impact is striking with changes in work patterns and community activities, such as traditional events, mutual cooperation and local traditions that face the challenges of change. The formation of new social strata creates inequalities in purchasing power, access to resources, and opportunities. This shows that mining affects the economy, culture and daily lives of people. On the other hand, economic or capital investment shows efforts to diversify income through establishing small businesses and investing in livestock businesses